The effectiveness of laser vitreolysis for vitreous floaters in posterior vitreous detachment. - Goh, Wan; Mustapha, Mushawiahti; Zakaria, Syed; Bastion, Mae-Lynn; Goh, Wan Ni; Zakaria, Syed Z S; Bastion, Mae-Lynn C (Indian Journal of Ophthalmology, 2022)
Purpose: To determine the effectiveness of laser vitreolysis in terms of contrast sensitivity function (CSF) and vision-related quality of life (VRQol) for symptomatic floaters due to posterior vitreous detachment (PVD).Materials: This is an interventional study that involved 57 eyes of 45 patients with symptomatic floaters for more than 3 months. Patients underwent one to three sessions of vitreolysis via Neodymiun-doped Yttrium Aluminum Garnet (Nd:YAG) laser. We examined the CSF using the computer programs Freiburg Acuity and Contrast Test (FrACT) and VRQoL survey using the National Eye Institute Visual Function Questionnaire-25 (NEI VFQ-25) before, and 1 month after, vitreolysis.Results: Twelve patients had both eyes lasered and 33 patients had one eye lasered. The mean CSF improved from 3.20 ± 0.85%W to 2.64 ± 0.63%W 1 month after vitreolysis. Each use of the laser showed a significant mean difference in CSF (%W) as analyzed by paired t-test before and after the first laser (0.29 ± 0.49%W [P ≤ 0.001]); after the first and second laser (0.35 ± 0.53%W [P = 0.01]); and after second and third laser (0.21 ± 0.31%W [P = 0.02]). There was improvement in the median of four subscales in NEI VFQ-25 scores post treatment: general vision (z = -3.30, P = 0.001), near activity (z = 3.396, P = 0.001, distance activity (z = -2.788, P = 0.005), and mental health (z = -2.219, P = 0.026). The mean scores increased to 79.55 ± 9.45 from the baseline 75.06 ± 9.69 (P ≤ 0.001). No adverse events were recorded 1 month after the laser treatments.Conclusion: Vitreolysis by Nd:YAG laser improved the CFS and VRQoL in symptomatic PVD patients.